Pericentromeric Satellite III transcripts induce etoposide resistance - Kanne, Julian; Hussong, Michelle; Isensee, Joerg; Munoz-Lopez, Alvaro; Wolffgramm, Jan; Hess, Felix; Grimm, Christina; Bessonov, Sergey; Meder, Lydia; Wang, Jie; Reinhardt, H. Christian; Odenthal, Margarete; et al. (Cell Death & Disease, 2021)
Non-coding RNA from pericentromeric satellite repeats are involved in stress-dependent splicing processes, maintenance of heterochromatin, and are required to protect genome stability. Here we show that the long non-coding satellite III RNA (SatIII) generates resistance against the topoisomerase IIa (TOP2A) inhibitor etoposide in lung cancer. Because heat shock conditions (HS) protect cells against the toxicity of etoposide, and SatIII is significantly induced under HS, we hypothesized that the protective effect could be traced back to SatIII. Using genome methylation profiles of patient-derived xenograft mouse models we show that the epigenetic modification of the SatIII DNA locus and the resulting SatIII expression predict chemotherapy resistance. In response to stress, SatIII recruits TOP2A to nuclear stress bodies, which protects TOP2A from a complex formation with etoposide and results in decreased DNA damage after treatment. We show that BRD4 inhibitors reduce the expression of SatIII, restoring etoposide sensitivity.
CRIS-Team Scopus Importer:2023-03-21